Evaluation of Ligand Competitive Ability for Binding in Mixed Ligand Complex - Jassim, Salah Aldin (Al-Nahrain Journal of Science)
In this work, several attempts were carried out to evaluate the formation of mixed ligand complex from 1-10 phenanthroline (phen.) and dimethylglyoxime (DMG) with zinc ion. Complex formation tested using both FTIR and1H NMR techniques supported by density functional theory calculations (DFT) to investigate the mulliken charges of both free ligands and their corresponding mixed ligand complex to determine the competitive ability of each ligand toward zinc ion and to study the possibility of the synthesis of mixed ligand complex. Results obtained show that 1-10 phen. ligand binds stronger than DMG. Octahedral geometry of the complex was observed involves 2:1 mole ratio of L:M in addition to 2 mole of chloride ion.